Flower therapy and perceived stress in primary health care nursing professionals: randomized clinical trial - Fabiana Gonçalves Seki Gava; Ruth Natália Teresa Turrini (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To analyze the effectiveness of Bach flower therapy compared to placebo in reducing perceived stress levels in primary health care nursing professionals. Method: Pragmatic, parallel randomized clinical trial conducted with 87 primary care nursing professionals with self-identified stress, from October 2021 to June 2022, in the cities of Osasco and São Paulo, Brazil. The intervention group (n=43) received the collective flower formula, and the placebo group (n=44) received only the diluent. Data analysis was performed using the linear mixed model, and effect size was measured by partial Eta squared, significance level 5%. Results: Data analysis showed a significant reduction in perceived stress levels within groups (p=0.038). However, there was no significant difference between the study groups (p=0.750). Participants in the intervention group reported a greater perception of changes than participants in the placebo group, but without statistical significance (p=0,089). Conclusion: The floral formula was not more effective than the placebo formula in reducing perceived stress. There was a significant stress reduction among nursing professionals in both study groups, although with a small effect size.